2019
DOI: 10.1080/20008198.2019.1605280
|View full text |Cite
|
Sign up to set email alerts
|

How does parental attachment contribute to post-traumatic growth among adolescents following an earthquake? Testing a multiple mediation model

Abstract: This study aimed to elucidate the mechanism underlying the effect of parental attachment on post-traumatic growth (PTG) among adolescents. Nine and a half years after the Wenchuan earthquake, 872 adolescents in China were assessed using self-reported questionnaires. The results showed that parental attachment had a direct association with PTG, two significant one-step indirect associations with PTG (through justice beliefs and cognitive reappraisal), two significant two-step indirect associations (through feel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…When one considers the frequency and intensity of distressing ANS stimuli that one might experience during acute PTSD symptoms (e.g., racing heart, shortness of breath, muscle tension, increased sweat secretion, etc. ), the increased regulatory capacity of the thalamus is paramount toward curating an internal sense of safety for a survivor, without which the process of PTG might be thwarted ( Zhou et al, 2019 ; Kapur et al, 2022 ). Lastly, the L precuneus, among its many functions, is often implicated in novel environmental information processing and integration as well as stressful cue reactivity inhibition ( Geuze et al, 2007 ; Sartory et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…When one considers the frequency and intensity of distressing ANS stimuli that one might experience during acute PTSD symptoms (e.g., racing heart, shortness of breath, muscle tension, increased sweat secretion, etc. ), the increased regulatory capacity of the thalamus is paramount toward curating an internal sense of safety for a survivor, without which the process of PTG might be thwarted ( Zhou et al, 2019 ; Kapur et al, 2022 ). Lastly, the L precuneus, among its many functions, is often implicated in novel environmental information processing and integration as well as stressful cue reactivity inhibition ( Geuze et al, 2007 ; Sartory et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PCL‐5 includes 20 items that are used to capture the severity and frequency of PTSD symptoms; in the present study, participants were asked to rate symptoms in relation to their COVID‐19–related experiences. Previous studies have validated the Chinese version of the PCL‐5 in adolescent samples (Zhou et al., 2019 , 2019b ). Participants were asked to rate the frequency of each symptom during the past 2 weeks, scoring responses on a scale of 0 ( not at all/only once ) to 4 ( almost every day ).…”
Section: Methodsmentioning
confidence: 99%
“…Items are scored on a 6-point scale ranging from 0 (no change) to 5 (a very great degree of change). The modified PTGI we used included 22 items on three subscales: Perceived Changes in Self (nine items, e.g., "I'm more likely to try to change things which need changing"), Changed Sense of Relationship With Others (seven items, e.g., "A sense of closeness with others"), and Changed Life Philosophy (six items, e.g., "An appreciation for the value of my own life"); this modified version has demonstrated good applicability in Chinese children and adolescents following trauma exposure (Zhou et al, 2019a(Zhou et al, , 2019b. In the present sample, the reliability of the modified PTGI was excellent, Cronbach's α = .92.…”
Section: Ptgmentioning
confidence: 99%
“…Specifically, result of the direct effect model showed that parent attachment at 12-month positively predicted PTG at 18-month, which was consistent with previous cross-sectional studies on the relationship between parental attachment and PTG. 21,32,41 Parent attachment reflects people's bonding with the primary caregiver in early life. Once formed, the attachment is relatively stable and could affect people's mental health in later life.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies reporting the concurrent relationships among the parental attachment, resilience, and PTG in adolescents by using the cross-sectional data following the tornado. 16,41 However, the longitudinal effects of parental attachment on resilience and PTG remain unknown. A longitudinal study is necessary to examine the causal links among the 3 variables.…”
mentioning
confidence: 99%